Literature Review on Junior Athlete Management: Injury Prevention, Rehabilitation, and Performance Optimization - Uray Nur Hidayat; Eka Supriatna; Maharani Fatima Gandasari (Indonesian Journal of Sport Management, 2025)
Background: Junior athlete management is essential for supporting young athletes, particularly in addressing injuries, prevention strategies, rehabilitation, and performance enhancement. Objective: This literature review aims to identify and analyze scientific findings related to injuries, prevention strategies, performance improvement, and nutrition in junior athletes. The literature search used the keyword “junior athlete management” across several scientific databases. Method: Based on Web of Science (WOS) data, 74 articles were initially identified. From these, 22 articles published in the last five years met the inclusion criteria, and 11 articles were selected for in-depth analysis due to their strong relevance to the topic. Results: The review indicates that research on junior athlete management predominantly focuses on injury incidence, treatment, and performance. Musculoskeletal injuries particularly to the ankles, knees, fingers, head, and lower extremities are the most common among young athletes. Impact-related injuries frequently occur in martial arts and boxing, while ACL injuries and ankle sprains are major concerns in high-intensity sports such as soccer. Prevention and rehabilitation strategies including the RICE method, kinesio taping, and video-based education or workshops have proven effective in improving injury management. Additionally, training programs that incorporate psychological components, effective communication, and professional coaching significantly support athlete motivation and performance. Conclusion: The integration of structured training programs, comprehensive injury prevention, and continuous management support forms the essential foundation for developing healthy, resilient, and high-performing junior athletes.